Ecosystems and human health toxicology and environmental hazards - Philp, Richard B. (CRC Press, 2013)
"The third edition of a bestseller, this book describes how chemical toxins and biological hazards impact the environment and people. Addressing how pollutants can alter the environment by contributing to global climate change, the author explores a broad range of environmental and health aspects of chemical and biological hazards. He includes numerous examples of the intimate relationship between ecosystem health and human health and emphasizes the need to consider this relationship whenever human activities are likely to have a significant environmental impact"-- Provided by publisher.
Keywords: Environmental toxicology.; Environmental health.; elektronické knihy; electronic books